Advances in pulmonary neuroendocrine cells and their cellular interactions in asthma pathogenesis - Wang, Lanlan; Wang, Hui; Yuan, Yamei; Ye, Weidong; Fang, Xiangming (Frontiers in Pharmacology, 2026)
Asthma is a complex chronic inflammatory airway disease, whose pathogenesis involves interactions among multiple cell types and molecular pathways. Pulmonary neuroendocrine cells (PNECs), rare epithelial cells in the lungs, have recently gained attention as pulmonary sensors. PNECs detect environmental signals and regulate pulmonary immune responses and physiological functions by releasing neuropeptides and neurotransmitters. Aberrant activation of PNECs is implicated in various respiratory diseases, including asthma, where they interact significantly with other cell types, such as type 2 innate lymphoid cells (ILC2s), goblet cells, and eosinophils. Recent studies have highlighted the potential of targeting PNEC-related pathways for developing novel anti-inflammatory drugs and identifying biomarkers to evaluate drug efficacy and toxicity in asthma. Exploring asthma pathogenesis through the functional characteristics of PNECs and their interactions with other cells could have potential clinical value in diagnosing and treating of asthma.